The comparatives as the pragmatic aspect of the world picture formation in humorous discourse of E. Hutsalo and A. Ilchenko - Ковальова, Ганна Миколаївна; Зубенко, Катерина В'ячеславівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article continues the course of authors’ publications, devoted to the study of humorous discourse pragmalinguistics in Ukrainian fanciful prose. The emphasized thought is that one of the most important assignments in the study of pragmatic means of linguistic world picture expression is, specifically, disclosure of essence of the creative author’s self-expression with the help of comparative constructions. The role of pragmatic significance of comparisons, taking into account verbal-semantic, linguo-cognitive and motivational levels in the process of disclosure of separate comparative unit functioning peculiarities according to the realization of the author’s intention.